Criminal Law Policy of the State on Criminalization and Decriminalization of Smuggling - Сорока, Світлана; Soroka, Svitlana (Видавництво Львівської політехніки, 2024)
У статті розглянуто питання кримінально-правової політики держави щодо криміналізації та декриміналізації контрабанди. Відзначено, що захист прав та свобод людини і громадянина є першочерговим завданням держави, яке реалізується через її кримінально-правову політику. Основними методами щодо реалізації кримінально-правової політики держави є визначення кола суспільно-небезпечних діянь, які законодавець зараховує до категорії кримінально-протиправних (криміналізація) та вилучення діяння з кола таких, які визнаються кримінально-протиправними (декриміналізація). Враховуючи, що з моменту прийняття чинного Кримінального кодексу України в статтях 201 і 305 КК України, які передбачають відповідальність за контрабанду, вносилось багато змін і доповнень, виникла потреба проаналізувати використання цих методів щодо застосування до вищезазначених статей. Акцентовано, що виникнення контрабанди має глибокі корені, проте воно було викликано об’єктивним наслідком економічного розвитку держави: в державі виникають матеріальні труднощі, що веде до обміну товарами, і відповідно ці відносини пов’язуються з митною політикою, проте контрабанда як правопорушення виникла в XIV–XVI століттях, коли почали інтенсивно розвиватись товарно-грошові відносини. В Україні, яка в той час перебувала у складі росії, законодавство щодо протидії контрабанді почало формуватися з середини XVII ст. і продовжується досі. Констатовано, що в Кримінальному кодексі України 2001 року відповідальність за контрабанду встановлена статтями 201 і 305 КК України, проте з моменту прийняття кодексу і до сьогодні законодавцем сім разів вносилися зміни і доповнення до цих статей, відповідно до останніх змін і доповнень: змінена назва ст. 201 КК України, яка звучить тепер “Контрабанда культурних цінностей та зброї”, а також КК України доповнено новими статтями: ст. 201-1 “Контрабанда лісоматеріалів та цінних порід дерев”, ст. 201-3 “Контрабанда товарів”, ст. 201-4. “Контрабанда підакцизних товарів”. Відповідно в статті проведено аналіз щодо зазначених змін і доповнень в кримінальному законодавстві. Зроблено висновок, що, проаналізувавши зміни, які вносились з моменту прийняття КК України у 2001 році, вважаємо, що на сьогодні законодавець значно розширив поняття контрабанди, визначивши додаткові предмети контрабанди, виділивши їх в окремі норми, але залишив єдиним для всіх складів поняття об’єктивної сторони контрабанди, яка незалежно від предмета контрабанди виражається в переміщенні предметів контрабанди поза митним контролем або з приховуванням від митного контролю, проте встановив різну міру кримінальної відповідальності з урахуванням предмета контрабанди.

The article discusses the issues of criminal law policy of the state regarding the criminalization and decriminalization of smuggling. It is noted that the protection of human and citizen rights and freedoms is the primary task of the state, which is implemented through its criminal and legal policy. The main methods for implementing the state’s criminal and legal policy include defining a range of socially dangerous acts that the legislator classifies as criminal (criminalization) and excluding acts from the category that are recognized as criminal (decriminalization). Considering that since the adoption of the current Criminal Code of Ukraine, there have been many changes and additions to Articles 201 and 305 of the Criminal Code of Ukraine, which provide for liability for smuggling, there is a need to analyze the use of these methods in relation to the aforementioned articles. It is emphasized that the emergence of smuggling has deep roots, but it was caused by the objective consequence of the economic development of the state: material difficulties arise in the state, leading to the exchange of goods, and accordingly, these relations are connected with customs policy. However, smuggling as a violation arose in the XIV–XVI centuries, when trade and monetary relations began to develop intensively. In Ukraine, which at that time was part of Russia, legislation regarding the counteraction to smuggling began to take shape from the middle of the XVII century and continues to the present day. It is stated that in the Criminal Code of Ukraine of 2001, liability for smuggling is established by Articles 201 and 305 of the Criminal Code of Ukraine, but since the adoption of the code and to this day, changes and additions have been made to these articles seven times. According to the latest changes and additions, the name of Article 201 of the Criminal Code of Ukraine has been changed to “Smuggling of cultural values and weapons”, and the Criminal Code of Ukraine has been supplemented with new articles: Article 201-1 “Smuggling of timber and valuable tree species”, Article 201-3 “Smuggling of goods”, Article 201-4 “Smuggling of excisable goods”. Accordingly, the article provides an analysis of the mentioned changes and additions in criminal legislation. It is concluded that by analyzing the changes that have been made since the adoption of the Criminal Code of Ukraine in 2001, it is concluded that today the legislator has significantly expanded the concept of smuggling, defining additional objects of smuggling, allocating them into separate norms, but leaving the objective side of smuggling as the only one for all compositions, which, regardless of the object of smuggling, is expressed in the movement of smuggled goods beyond customs control or in concealing them from customs control, but establishing different degrees of criminal liability, taking into account the object of smuggling.
Кримінально-правова політика держави щодо криміналізації та декриміналізації контрабанди
Keywords: кримінально-правова політика; контрабанда; предмети контрабанди; криміналізація; декриміналізація; законодавство про кримінальну відповідальність; criminal and legal policy; smuggling; objects of smuggling; criminalization; decriminalization; legislation on criminal liability; 343.575(477)